IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS DALAM MENUMBUHKAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Cahyono Cahyono (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aims to determine the effect on students' learning motivation through the implementation of the Teams Games Tournament cooperative learning model. Lack of student learning motivation, especially in the subjects of Pancasila and citizenship education, one of the reasons is the weakness of the learning process in the classroom, for example, many teachers still apply conventional methods when the learning process takes place in the classroom, and this is one of the backgrounds behind the problems in this study. This research uses descriptive study method and uses a qualitative approach. Data collection used is through interviews and literature studies. The population in this study were all students of SMPN 1 Rancaekek, and the samples of this study were students in class VII A and VII B. Through interviews with the Pancasila and Nationality education teachers and student representatives, it was found that there was a learning process that involved all students namely by implementing learning gamesbased learning, the application of the learning model makes learning activities in the classroom more active and innovative so that it gives an influence on the learning motivation of participants. So it can be concluded that the implementation of the Teams Games Tournament learning model has an effect on increasing student learning motivation in Pancasila and citizenship education subjects.